Atomic-scale insight into the pyrolysis of polycarbonate by ReaxFF-based reactive molecular dynamics simulation. (1st March 2021) - Liu, Qiang; Liu, Shixiang; Lv, Yadong; Hu, Ping; Huang, Yajiang; Kong, Miqiu; Li, Guangxian
Graphical abstract: Highlights: Experiments and simulations uncovered the pyrolysis mechanisms of polycarbonate. Density functional theory and experiments validated the applicability of ReaxFF. ReaxFF simulations revealed available and new chemical reactions. The pyrolysis kinetics of polycarbonate was investigated. The reduction of carbon dioxide and isomerization of isopropylidene were revealed. Abstract: The isothermal pyrolysis behavior of bisphenol-A polycarbonate under anoxic conditions at different temperatures was studied by using molecular dynamics simulations with a reactive force field (ReaxFF) and compared with experiment results. The main pyrolysis products of polycarbonate observed in the actual pyrolysis experiments were well reproduced by ReaxFF simulations. The applicability and reliability of the ReaxFF force field were validated by the density functional theory and experiments. Kinetics study showed that the pyrolysis of polycarbonate was predominated by random chain scission and carbonate groups were more vulnerable to high temperatures than isopropylidene groups. The reaction routes of various pyrolysis products and related secondary reactions were revealed by ReaxFF simulations. The ether linkages can be formed by a concerted process or a radical process based on different reaction mechanisms. Cyclic oligomers, hydrolysis, and transesterification seldom took place at extremely high temperatures. Ultimately, the main thermolysis mechanisms of polycarbonate without oxygen were outlined.